RESEARCH ON RELIABILITY OF SHEARER’ROCKER SHELL BASED ON VP AND BP NEURAL NETWORK - ZHAO LiJuan; ZHAO MingYang; LIU XuNan (Jixie qiangdu)
In order to improve dynamic reliability and work efficiency of shearer,the rigid-flexible coupling model of SL1000 shearer was constructed,the stress and reliability information of rocker shell were obtained through dynamic simulation;Based on BP neural network,the rocker arm shell’reliability of other conditions were predicted,and the relationship between it and coal seams consistent coefficient、tract Dion speed、roller cutting depth were analyzed,and the traction speed of shearer was optimized. The combination of virtual prototyping technology and BP neural network provides a new concept and convenient method for the prediction of shearer’work reliability,and it has important theoretical significance and engineering application value.